2020
DOI: 10.1136/bmjstel-2020-000631
|View full text |Cite
|
Sign up to set email alerts
|

Biosensors, Biomarkers and Biometrics: a Bootcamp Perspective

Abstract: IntroductionCompetitive physical performance is routinely monitored by wearable technology (biosensors), yet professional healthcare is not, despite high prevalence of trainee stress and burnout, notwithstanding the corresponding risk to patient safety. This study aimed to document the physiological stress response of UK Core Surgical Trainees (CSTs) during simulation training.MethodsCSTs (n=20, 10 male) were fitted with Vital Scout Wellness Monitors (VivaLNK, Campbell, California, USA) for an intensive 3-day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…For example, Wu et al found that using cognitive and behavioral metrics through EEG and eye-metrics, with machine-learning can predict training outcomes with a 72.5% accuracy 110 . EEG features can also detect high CogL and altered performance during training 44,57,110–113 . Optimizing CogL in trainees can improve their capacity for learning and progression 114–116 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wu et al found that using cognitive and behavioral metrics through EEG and eye-metrics, with machine-learning can predict training outcomes with a 72.5% accuracy 110 . EEG features can also detect high CogL and altered performance during training 44,57,110–113 . Optimizing CogL in trainees can improve their capacity for learning and progression 114–116 .…”
Section: Discussionmentioning
confidence: 99%
“…110 EEG features can also detect high CogL and altered performance during training. 44,57,[110][111][112][113] Optimizing CogL in trainees can improve their capacity for learning and progression. [114][115][116] In one example, Maimon et al (2022) used CogL levels via EEG in simulation to assess if a trainee was "ready" to operate on a live patient.…”
Section: Applications Of Surgical Sabermetricsmentioning
confidence: 99%
“…8 James et al have recently demonstrated that such devices are practical for assessment of physiological variables among Core Surgical Trainees, during a 3-day training boot camp (including simulated practical tasks), and therefore this gives an indication that wearable technology could offer a practical solution to monitoring physiological parameters of medical professionals in the clinical setting. 9…”
Section: Introductionmentioning
confidence: 99%